Manpower Training and Development in Nigeria Public Organisations: A Study of Abia State Civil Service. (International Journal of Scientific Research and Management (IJSRM), 2022)
Manpower training and development is essential to the success and productivity of every organization. Although technology and the internet have enabled global collaboration and competition, employees are still the organization’s competitive advantage. Manpower training and development enables employees to develop skills and competence necessary to enhance bottom-line results for their organizations.